Collaboration between users and the institution of public health as the basis in successful strategic management (Italian Journal of Public Health, 2009)
Background: The improvement of management in healthcare system is one of the basic goals of the modernmanagement style of Serbia. Among the most significant institutions of public healthcare is the Institute ofPublic Health, which has a long tradition within the country.Methods: This cross-sectional study was conducted from December 2007 to January 2008 at the Institutionof Public Health (IPH) in Kikinda. The study involved a population from the North Banat district, who, at thetime, used some of the Institution’s services: hygienic-ecological, epidemiological, and microbiological. Theinstrument of the study was a questionnaire which was used to assess the opinion of the users of theInstitution’s services in terms of the performance and the quality of the services provided.Results: The relation between political factors in the country and the public health services provided washighly assessed by the responders, with the highest influence being attributed to the changes in thegovernment, i.e. state elections, and the lowest to the local authorities. The responders were satisfied withthe quality of the provided services but satisfaction regarding the collaboration between the IPH and variousregional organizations was lower. The social factors, population aging and multicultural environment, wereevaluated as being the most significant for the performance of the IPH.Conclusions: The identification of population needs and requirements for active inclusion in resolving priorityproblems should incorporate in the strategic management of public healthcare institutions, which would leadto the achievement of defined goals, as well as to the improved satisfaction of the users.
Keywords: strategic management; public health; users